Design, development and application of protein-templated gold nanoclusters in biosensing of glutathione, sodium and potassium ions - Wong, Xin Yi (2021)
Protein-templated gold nanoclusters (AuNCs) are emerging nanomaterials with diverse applications in biomedical fields. AuNCs display discrete energy levels, large Stokes shift, good water solubility, distinctive fluorescence properties, high photostability and biocompatibility. These features make AuNCs a perfect candidate for imaging, biosensing and theranostics in the cellular and molecular level.